A two-phase hybrid fiber bulletproof composite material based on lamination sequence optimization and a preparation method thereof
Patent Information
- Application Number
- CN202611357162.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-27
AI Technical Summary
其中芳纶纤维具有高模量、高剪切强度、良好的耐热性和阻燃性,但其密度较高(1.44g/cm3),且对紫外线和湿热环境敏感,长期使用性能下降
(1)本发明通过迎弹面、过渡层、背弹面功能分区梯度叠层结构,充分发挥芳纶高抗剪切、超高分子量聚乙烯高吸能的优势,交替过渡层有效缓解模量突变与应力集中,从结构上解决传统混杂复合材料易分层、应力传递不连续的问题,显著提升弹道防护稳定性与结构整体性。
Smart Images

Figure CN122976145A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber bulletproof composite materials technology, and in particular to a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence and its preparation method. Background Technology
[0002] Resin-based continuous fiber composites have been widely used in military and civilian protective applications such as individual body armor, bulletproof inserts, lightweight armor, and protective enclosures due to their advantages such as high specific strength, high specific modulus, low density, and strong energy absorption capacity. Currently, commonly used bulletproof fiber materials mainly include aramid fiber, ultra-high molecular weight polyethylene fiber, carbon fiber, poly(p-phenylenebenzobisoxazole) fiber, and polypyridodiimidazole fiber. Among them, aramid fiber has high modulus, high shear strength, good heat resistance, and flame retardancy, but its density is relatively high (1.44 g / cm³). 3 It is also sensitive to ultraviolet radiation and humid environments, and its performance deteriorates with long-term use. Ultra-high molecular weight polyethylene fiber has an extremely low density (0.97 g / cm³). 3 It has extremely high specific strength and specific modulus, high elongation at break (3.5%), and excellent energy absorption capacity, but it has poor creep resistance, low melting temperature (about 138℃), weak shear resistance, strong surface chemical inertness, and low interfacial bonding strength with the resin matrix.
[0003] In order to give full play to the performance advantages of the two fibers, researchers tried to hybridize aramid fiber with ultra-high molecular weight polyethylene. Although the interlaminar fracture toughness of the composite material was improved to a certain extent, the following technical problems still exist: (1) A simple alternating layup method was adopted, but the functional partition design in the direction of projectile penetration was not considered, resulting in a significant change in modulus between the projectile-facing surface and the projectile-backing surface, which easily leads to interlaminar delamination during impact; (2) The fiber surface was not systematically modified, the interfacial bonding strength between the fiber and the resin was insufficient, and the ballistic limit velocity was limited; (3) The matrix resin is mostly a conventional epoxy system, lacking interlaminar toughening design. During the impact, cracks are easy to propagate rapidly along the interlaminar layer, and the overall anti-delamination performance of the composite material is poor.
[0004] Therefore, developing a hybrid bulletproof composite material of aramid fiber and ultra-high molecular weight polyethylene that can systematically solve the above problems has important application value. Summary of the Invention
[0005] The purpose of this invention is to provide a two-phase hybrid fiber ballistic composite material based on optimized lamination sequence and its preparation method. Through functional partitioning gradient lamination structure, fiber surface composite modification, nano-silica coating to suppress slip, and resin two-component micron particles for synergistic toughening, the ballistic protection performance, anti-delamination performance and structural service stability of the composite material are significantly improved. The preparation process is simple and controllable and the raw materials are readily available.
[0006] To achieve the above objectives, the present invention provides a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence. The bulletproof composite material is composed of a reinforcing fiber layer and a matrix resin impregnated between the layers. The reinforcing fiber layer includes a projectile-facing surface, a transition layer, and a projectile-backing surface along the projectile penetration direction. The projectile-facing surface is composed of several layers of modified aramid fiber, the projectile-backing surface is composed of several layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer is composed of several layers of modified aramid fiber and several layers of modified ultra-high molecular weight polyethylene fiber, which are alternately layered. The matrix resin includes epoxy resin and toughening components.
[0007] Preferably, the modified aramid fiber layer is an aramid fiber that has been surface modified by oxygen plasma and silane coupling agent, and the surface of the modified aramid fiber layer is coated with multi-walled carbon nanotubes.
[0008] Preferably, the modified ultra-high molecular weight polyethylene fiber layer is an ultra-high molecular weight polyethylene fiber impregnated with a nano-silica dispersion, and the nano-silica dispersion is an ethanol dispersion of nano-silica.
[0009] Preferably, the toughening component accounts for 3%-5% of the mass fraction of the matrix resin, and the toughening component is composed of polyetherimide microparticles and diphenylmethane bismaleimide micro powder in a mass ratio of (2-3):1.
[0010] This invention also provides a method for preparing the above-mentioned two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, comprising the following steps: S1. Aramid fibers are treated with oxygen plasma, then immersed in an ethanol solution of silane coupling agent, removed and vacuum dried to obtain a modified aramid fiber layer. Then, an ethanol dispersion of multi-walled carbon nanotubes is sprayed onto the modified aramid fiber layer and allowed to evaporate and dry naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes. S2. Place ultra-high molecular weight polyethylene fibers in a nano-silica dispersion, ultrasonically impregnate and then mold, and vacuum dry to obtain a modified ultra-high molecular weight polyethylene fiber layer. S3. After mixing the epoxy resin and allyl compound evenly, add the toughening component, mix evenly, add the low-temperature curing agent, and degas under vacuum to obtain the matrix resin. S4. A modified ultra-high molecular weight polyethylene fiber layer, a modified aramid fiber layer, and a modified ultra-high molecular weight polyethylene fiber layer are sequentially and alternately laid in a transition layer, and a modified aramid fiber layer, from the back elastic surface to the front elastic surface, to obtain a reinforcing fiber layer. S5. Lay a release cloth in a vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, draw a vacuum, and inject the matrix resin of S3 into the mold through the guide pipe so that the matrix resin evenly wets the reinforcing fiber layer; cure at a constant temperature, and cool to room temperature with the furnace to obtain the bulletproof composite material.
[0011] Preferably, in S1, the oxygen plasma treatment is performed at 100-200W for 3-7 minutes, the mass concentration of the ethanol solution of the silane coupling agent is 1%-3%, the impregnation time is 20-40 minutes, and the vacuum drying is performed at 70-90℃ for 0.5-2 hours. The mass concentration of the ethanol dispersion of multi-walled carbon nanotubes was 0.8%-1.2%, and it was uniformly sprayed onto the surface of the modified aramid fiber layer using a pneumatic spray gun.
[0012] Preferably, in S2, the mass concentration of the nano-silica dispersion is 15%-35%, the ultrasonic impregnation time is 10-15 min, the molding is performed at 1-3 MPa for 10-30 min, and the vacuum drying is performed at 70-80℃ for 20-24 h.
[0013] Preferably, in S3, the allyl compound is diallyl bisphenol A, and the mass ratio of the allyl compound to the epoxy resin is 1:(4-5); the low-temperature curing agent includes one of cashew nut shell oil modified phenolic amine, phenol modified phenolic amine, and cresol modified phenolic amine, and the mass ratio of the epoxy resin to the low-temperature curing agent is 100:(30-40), and the vacuum degassing time is 20-30 min.
[0014] Preferably, in S4, the ratio of the number of modified ultra-high molecular weight polyethylene fiber layers to the number of modified aramid fiber layers is (1-2):1, and the transition layer accounts for 20%-30% of the total number of reinforcing fiber layers.
[0015] Preferably, in S5, the vacuum is drawn to 0.2-0.3 MPa, and the constant temperature curing is carried out at 50-60℃ for 3-4 hours.
[0016] Therefore, the present invention employs the above-mentioned two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence and its preparation method, which has the following beneficial effects: (1) This invention fully utilizes the advantages of aramid's high shear resistance and ultra-high molecular weight polyethylene's high energy absorption through a functional partitioned gradient stacked structure of the anti-ballistic surface, transition layer and back ballistic surface. The alternating transition layer effectively alleviates the sudden change in modulus and stress concentration, and structurally solves the problems of easy delamination and discontinuous stress transmission in traditional hybrid composite materials, thus significantly improving the stability of ballistic protection and the integrity of the structure.
[0017] (2) In this invention, aramid is modified by plasma and coupling agent, and multi-walled carbon nanotubes are sprayed to construct a nano-reinforced network, which greatly improves the interfacial bonding strength and interlayer toughness; ultra-high molecular weight polyethylene is impregnated with nano-silica to increase the surface roughness and frictional resistance of the fiber, effectively suppress fiber slippage under impact, and significantly improve energy absorption and ballistic impact resistance.
[0018] (3) The present invention adopts polyetherimide and bismaleimide micro powder as two components for synergistic toughening, combined with low temperature vacuum injection molding process, which ensures that the interlayer toughness and interface strength are greatly improved while avoiding fiber thermal damage, resulting in high molding quality and stable process; the final composite material has the advantages of high ballistic limit, low back convex deformation and lightweight, and its comprehensive performance is superior to the traditional solution, making it highly practical.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 These are schematic diagrams illustrating the interlaminar shear strength of Embodiments 1-3 and Comparative Examples 1-5 of the present invention; Figure 2 These are schematic diagrams of the interlaminar fracture toughness of Embodiments 1-3 and Comparative Examples 1-5 of the present invention. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0022] This invention provides a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence. The bulletproof composite material is composed of a reinforcing fiber layer and a matrix resin impregnated between the layers. The reinforcing fiber layer includes a projectile-facing surface, a transition layer, and a projectile-backing surface along the projectile penetration direction. The projectile-facing surface is composed of several layers of modified aramid fiber, the projectile-backing surface is composed of several layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer is composed of several layers of modified aramid fiber and several layers of modified ultra-high molecular weight polyethylene fiber, which are alternately layered. The matrix resin includes epoxy resin and toughening components.
[0023] The bulletproof composite material of this invention adopts a functional zoning design with a high modulus shear resistance on the projectile-facing surface and a high toughness energy absorption on the projectile-receiving surface. The projectile-facing surface is composed of a modified aramid fiber layer, which utilizes the high modulus and high shear strength of aramid fibers to achieve rapid stress wave transmission and localized small-scale damage in the early stage of projectile impact, and suppress large-area matrix and fiber cracking. The transition layer is composed of alternating layers of modified aramid fibers and modified ultra-high molecular weight polyethylene fibers to form a gradient transition of mechanical properties, avoiding stress concentration and interlayer delamination caused by abrupt changes in modulus between the projectile-facing and projectile-receiving surfaces. The projectile-receiving surface is composed of a modified ultra-high molecular weight polyethylene fiber layer, which utilizes the high elongation at break and high toughness of ultra-high molecular weight polyethylene fibers to fully absorb the remaining kinetic energy of the projectile through large transverse tensile deformation, while controlling the back convex deformation within a safe threshold (≤25mm). The matrix resin contains epoxy resin and toughening components, which, while transmitting stress and fixing fiber positions, significantly improve interlayer fracture toughness through the enrichment effect of toughening components at the interlayer interface.
[0024] Preferably, the modified aramid fiber layer is an aramid fiber that has been surface modified by oxygen plasma and silane coupling agent, and the surface of the modified aramid fiber layer is coated with multi-walled carbon nanotubes.
[0025] A further preferred option is KH550 silane coupling agent.
[0026] The surface-modified aramid fiber layer of this invention introduces polar functional groups such as hydroxyl and carboxyl groups on the fiber surface through oxygen plasma treatment, which significantly improves the surface activity of the fiber. Subsequently, the silane coupling agent is impregnated to form chemical bonds between the coupling agent molecules and the fiber surface, constructing a molecular bridge between the fiber and the resin matrix and improving the interfacial shear strength. This effectively overcomes the inherent defects of aramid fiber surface chemical inertness, poor resin wettability, and low interfacial bonding strength.
[0027] Multi-walled carbon nanotubes coated on the surface form a uniform and continuous nano-reinforcing network on the surface of the aramid fiber layer. The multi-walled carbon nanotubes are anchored to the fiber surface in the form of nano-nails. The carbon nanotubes dissipate a large amount of energy through mechanisms such as pull-out, fracture and interface slip, thereby improving the interlaminar fracture toughness of the bulletproof composite material. This overcomes the problem of insufficient interlaminar toughness and easy delamination cracking of pure aramid composite materials under impact.
[0028] Preferably, the modified ultra-high molecular weight polyethylene fiber layer is an ultra-high molecular weight polyethylene fiber impregnated with a nano-silica dispersion, and the nano-silica dispersion is an ethanol dispersion of nano-silica.
[0029] This invention modifies the ultra-high molecular weight polyethylene (UHMWPE) fiber layer by impregnation with a nano-silica dispersion, allowing the dispersion to penetrate uniformly into the fiber bundle and forming a nano-composite coating on the surface of each UHMWPE fiber. The nano-silica particles form a micro-nano scale rigid protrusion structure on the fiber surface, significantly increasing the surface roughness of the UHMWPE fiber and enhancing the mechanical interlocking effect between the UHMWPE fiber and the resin matrix. After the composite material cures, the nano-silica particles on adjacent fiber surfaces come into contact with each other, forming a particle-particle point contact interface. Under impact load, the sliding friction between the particles effectively inhibits slippage and pull-out of the UHMWPE fiber. Simultaneously, the rigid nano-silica particles act as stress concentration points, transferring localized stress to the surrounding fibers and resin matrix during impact, promoting uniform stress distribution, effectively inhibiting monofilament slippage and interlaminar displacement of the UHMWPE fiber, improving interfacial bonding strength and energy dissipation capacity, and compensating for the inherent defects of UHMWPE fiber's weak shear resistance and easy slippage. This improves the overall ballistic impact resistance and anti-delamination performance of the composite material.
[0030] Preferably, the toughening component accounts for 3%-5% of the mass fraction of the matrix resin, and the toughening component is composed of polyetherimide microparticles and diphenylmethane bismaleimide micro powder in a mass ratio of (2-3):1.
[0031] Preferably, the epoxy resin includes one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and alicyclic epoxy resin; all of which are well compatible with low-temperature curing agents, have low curing shrinkage, excellent wettability, and high bonding strength; at the same time, they are suitable for 50-60℃ low-temperature curing processes, which will not cause thermal damage to ultra-high molecular weight polyethylene fibers, and meet the requirements of high interfacial strength, low porosity, and impact resistance of bulletproof composite materials.
[0032] In this invention, the toughening components are uniformly dispersed in the epoxy resin matrix. The polyetherimide microparticles inhibit crack propagation and absorb impact energy through plastic deformation, while the diphenylmethane bismaleimide micropowder improves the resin processability and enhances the interlayer bonding strength after curing. The two work together to achieve the toughening of the resin system.
[0033] This invention also provides a method for preparing the above-mentioned two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, comprising the following steps: S1. Aramid fibers are treated with oxygen plasma, then immersed in an ethanol solution of silane coupling agent, removed and vacuum dried to obtain a modified aramid fiber layer. Then, an ethanol dispersion of multi-walled carbon nanotubes is sprayed onto the modified aramid fiber layer and allowed to evaporate and dry naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes. S2. Place ultra-high molecular weight polyethylene fibers in a nano-silica dispersion, ultrasonically impregnate and then mold, and vacuum dry to obtain a modified ultra-high molecular weight polyethylene fiber layer. S3. After mixing the epoxy resin and allyl compound evenly, add the toughening component, mix evenly, add the low-temperature curing agent, and degas under vacuum to obtain the matrix resin. S4. A modified ultra-high molecular weight polyethylene fiber layer, a modified aramid fiber layer, and a modified ultra-high molecular weight polyethylene fiber layer are sequentially and alternately laid in a transition layer, and a modified aramid fiber layer, from the back elastic surface to the front elastic surface, to obtain a reinforcing fiber layer. S5. Lay a release cloth in a vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, draw a vacuum, and inject the matrix resin of S3 into the mold through the guide pipe so that the matrix resin evenly wets the reinforcing fiber layer. Curing is carried out at a constant temperature and then cooled to room temperature in the furnace to obtain the bulletproof composite material.
[0034] Preferably, in S1, the oxygen plasma treatment is performed at 100-200W for 3-7 minutes, the mass concentration of the ethanol solution of the silane coupling agent is 1%-3%, the impregnation time is 20-40 minutes, and the vacuum drying is performed at 70-90℃ for 0.5-2 hours. The mass concentration of the ethanol dispersion of multi-walled carbon nanotubes was 0.8%-1.2%, and it was uniformly sprayed onto the surface of the modified aramid fiber layer using a pneumatic spray gun.
[0035] Preferably, in S2, the mass concentration of the nano-silica dispersion is 15%-35%, the ultrasonic impregnation time is 10-15 min, the molding is performed at 1-3 MPa for 10-30 min, and the vacuum drying is performed at 70-80℃ for 20-24 h.
[0036] Preferably, in S3, the allyl compound is diallyl bisphenol A, and the mass ratio of the allyl compound to the epoxy resin is 1:(4-5); the low-temperature curing agent includes one of cashew nut shell oil modified phenolic amine, phenol modified phenolic amine, and cresol modified phenolic amine, and the mass ratio of the epoxy resin to the low-temperature curing agent is 100:(30-40), and the vacuum degassing time is 20-30 min.
[0037] In a further preferred embodiment, in S3, the toughening component is first added to polyetherimide microparticles, and premixed evenly at 70-80℃. Then, diphenylmethane bismaleimide micropowder is added, and after further mixing, it is placed on a three-roll mill for physical blending 2-3 times. The polyetherimide microparticles and diphenylmethane bismaleimide micropowder are evenly dispersed by shearing and diffusion.
[0038] This invention introduces two types of micron-scale particles, polyetherimide microparticles and diphenylmethane bismaleimide microparticles, into the matrix resin. By utilizing the sieving effect of fiber bundles on solid particles during the vacuum-assisted resin transfer molding prepreg composite process, the toughening components are selectively enriched in the interface region between the reinforcing fiber layers, forming an interlayer toughening layer enriched with micron-scale particles.
[0039] In this invention, polyetherimide microparticles are thermoplastic high-performance engineering plastics with a particle size range of 10-50 μm. During the crack propagation process of projectile impact, they undergo plastic deformation and yielding, absorbing a large amount of energy through the plastic deformation mechanism, while inducing crack deflection and bifurcation, significantly improving the fracture toughness of the bulletproof composite material. Diphenylmethane bismaleimide micropowder is a thermosetting bismaleimide resin monomer with a particle size range of 10-50 μm. During the curing process, it undergoes a cross-linking reaction with allyl compounds and is enriched on the interlayer surface under the filtration of fibers. It enhances the interlayer bonding force through in-situ polymerization, and its rigid structure endows the interlayer interface with high modulus and shear resistance, forming a synergistic toughening effect with the toughness of polyetherimide microparticles. The combination of the two ensures both sufficient plastic deformation energy absorption units (polyetherimide microparticles) and rigid support and in-situ reinforcement effect of the interlayer interface (diphenylmethane bismaleimide micropowder). The synergistic effect of the two significantly improves the interlayer fracture toughness.
[0040] Preferably, in S4, the ratio of the number of modified ultra-high molecular weight polyethylene fiber layers to the number of modified aramid fiber layers is (1-2):1, and the transition layer accounts for 20%-30% of the total number of reinforcing fiber layers.
[0041] This invention controls the layer ratio within the aforementioned range, which fully leverages the respective advantages of aramid's high shear resistance and ultra-high molecular weight polyethylene's high energy absorption. The aramid on the impact-facing side effectively resists impact shear damage, while the ultra-high molecular weight polyethylene on the back-facing side fully dissipates impact kinetic energy. The alternating transition layer with a ratio of 20%-30% can smooth out the differences in modulus and mechanical properties between the two fibers, eliminate abrupt mechanical changes between layers, alleviate interface stress concentration, and prevent early delamination and cracking of the composite material when subjected to impact. This makes the overall stress transmission more continuous and improves the overall structural stability and ballistic protection performance.
[0042] Preferably, in step S5, the vacuum is evacuated to 0.2-0.3 MPa, and the constant temperature curing is carried out at 50-60℃ for 3-4 hours. Existing technology can be used for the vacuum-assisted resin transfer molding mold, and no further limitations are imposed.
[0043] By evacuating the vacuum to the aforementioned range, this invention can fully eliminate interlayer air and bubbles, ensuring that the matrix resin uniformly impregnates each fiber layer and reducing internal porosity defects. The low-temperature curing process of 50-60℃ can not only meet the requirements for complete cross-linking and curing of epoxy resin, but also avoid the problems of thermal creep and mechanical property degradation of ultra-high molecular weight polyethylene fibers due to high temperature. At the same time, it ensures a high degree of resin cross-linking and tight interfacial bonding, further improving the overall density, interlayer bonding strength and long-term stability of the composite material.
[0044] Example 1 This invention provides a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, composed of reinforcing fiber layers and a matrix resin impregnated between the layers. The reinforcing fiber layers, along the projectile penetration direction, include a projectile-facing surface, a transition layer, and a projectile-backing surface. The projectile-facing surface consists of 12 layers of modified aramid fiber, the projectile-backing surface consists of 18 layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer consists of 10 layers, alternating between one layer of modified aramid fiber and one layer of modified ultra-high molecular weight polyethylene fiber. The matrix resin includes bisphenol A type epoxy resin and a toughening component. The toughening component accounts for 3% of the mass fraction of the matrix resin and is composed of polyetherimide microparticles and diphenylmethane bismaleimide micropowder in a mass ratio of 2:1.
[0045] The preparation method of the above-mentioned bulletproof composite material includes the following steps: S1. Aramid fibers were subjected to oxygen plasma treatment at 100W for 7 min, followed by immersion in an ethanol solution of 1% KH550 silane coupling agent for 40 min. After removal, the fibers were vacuum dried at 70℃ for 2 h to obtain a modified aramid fiber layer. Then, an ethanol dispersion of 0.8% multi-walled carbon nanotubes was uniformly sprayed onto the modified aramid fiber layer using a pneumatic spray gun, and allowed to evaporate naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes.
[0046] S2. Place ultra-high molecular weight polyethylene fibers in a 15% (w / w) nano-silica dispersion, ultrasonically impregnate for 15 min, then mold under 1 MPa for 30 min, and finally vacuum dry at 70°C for 24 h to obtain a modified ultra-high molecular weight polyethylene fiber layer.
[0047] S3. After mixing bisphenol A type epoxy resin and diallyl bisphenol A at a mass ratio of 1:4, add polyetherimide micron particles and stir at 70°C to premix evenly. Then add diphenylmethane bismaleimide micro powder and continue stirring evenly. Place the mixture on a three-roll mill for physical mixing twice. Add cashew nut shell oil modified phenolic amine at a mass ratio of epoxy resin to low-temperature curing agent of 100:30 and degas under vacuum for 20 minutes to obtain the matrix resin.
[0048] S4. From the back elastic surface to the front elastic surface, 18 layers of modified ultra-high molecular weight polyethylene fiber, 5 layers of modified aramid fiber and 5 layers of modified ultra-high molecular weight polyethylene fiber are laid in sequence as a transition layer, and 12 layers of modified aramid fiber are laid in sequence to obtain the reinforcing fiber layer.
[0049] S5. Lay a release cloth in a vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, evacuate to 0.2MPa, inject the matrix resin of S3 into the mold through the guide pipe, so that the matrix resin uniformly wets the reinforcing fiber layer; cure at 50℃ for 3h, and cool to room temperature with the furnace to obtain the bulletproof composite material.
[0050] Example 2 This invention provides a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, composed of reinforcing fiber layers and a matrix resin impregnated between the layers. The reinforcing fiber layers, along the projectile penetration direction, include a projectile-facing surface, a transition layer, and a projectile-backing surface. The projectile-facing surface consists of 14 layers of modified aramid fiber, the projectile-backing surface consists of 20 layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer consists of 8 layers, alternating between one layer of modified aramid fiber and one layer of modified ultra-high molecular weight polyethylene fiber. The matrix resin includes bisphenol F epoxy resin and a toughening component. The toughening component accounts for 4% of the matrix resin by mass and is composed of polyetherimide microparticles and diphenylmethane bismaleimide micropowder in a mass ratio of 2.5:1.
[0051] The preparation method of the above-mentioned bulletproof composite material includes the following steps: S1. Aramid fibers were subjected to oxygen plasma treatment at 150W for 5 min, followed by immersion in an ethanol solution of 2% KH550 silane coupling agent for 30 min. After removal, the fibers were vacuum dried at 80℃ for 1 h to obtain a modified aramid fiber layer. Then, an ethanol dispersion of 1.0% multi-walled carbon nanotubes was uniformly sprayed onto the modified aramid fiber layer using a pneumatic spray gun, and allowed to evaporate naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes.
[0052] S2. Place ultra-high molecular weight polyethylene fibers in a 25% (w / w) nano-silica dispersion, ultrasonically impregnate for 12 min, then mold under 2 MPa for 20 min, and finally vacuum dry at 75°C for 22 h to obtain a modified ultra-high molecular weight polyethylene fiber layer.
[0053] S3. After mixing bisphenol F type epoxy resin and diallyl bisphenol A at a mass ratio of 1:5, add polyetherimide micron particles and stir at 75°C to premix evenly. Then add diphenylmethane bismaleimide micro powder and continue to stir evenly. Place the mixture on a three-roll mill for physical mixing 3 times. Add phenol-modified phenolic amine at a mass ratio of epoxy resin to low-temperature curing agent of 100:35 and degas under vacuum for 25 minutes to obtain the matrix resin.
[0054] S4. From the back surface to the front surface, 20 layers of modified ultra-high molecular weight polyethylene fiber, 4 layers of modified aramid fiber and 4 layers of modified ultra-high molecular weight polyethylene fiber are laid alternately as a transition layer, and 14 layers of modified aramid fiber are laid to obtain the reinforcing fiber layer.
[0055] S5. Lay a release cloth in a vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, evacuate to 0.3MPa, inject the matrix resin of S3 into the mold through the guide pipe, so that the matrix resin uniformly wets the reinforcing fiber layer; cure at 55℃ for 4h, and cool to room temperature with the furnace to obtain the bulletproof composite material.
[0056] Example 3 This invention provides a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, composed of reinforcing fiber layers and a matrix resin impregnated between the layers. The reinforcing fiber layers, along the projectile penetration direction, include a projectile-facing surface, a transition layer, and a projectile-backing surface. The projectile-facing surface consists of 15 layers of modified aramid fiber, the projectile-backing surface consists of 22 layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer consists of 10 layers, alternating between one layer of modified aramid fiber and one layer of modified ultra-high molecular weight polyethylene fiber. The matrix resin includes an alicyclic epoxy resin CELLOXIDE 2021P and a toughening component. The toughening component accounts for 5% of the matrix resin by mass and is composed of polyetherimide microparticles and diphenylmethane bismaleimide micropowder in a mass ratio of 3:1.
[0057] The preparation method of the above-mentioned bulletproof composite material includes the following steps: S1. Aramid fibers were subjected to oxygen plasma treatment at 200W for 3 min, followed by immersion in an ethanol solution of 1% KH550 silane coupling agent for 20 min. After removal, the fibers were vacuum dried at 90℃ for 0.5 h to obtain a modified aramid fiber layer. Then, an ethanol dispersion of 1.2% multi-walled carbon nanotubes was uniformly sprayed onto the modified aramid fiber layer using a pneumatic spray gun, and allowed to evaporate naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes.
[0058] S2. Place ultra-high molecular weight polyethylene fibers in a 35% (w / w) nano-silica dispersion, ultrasonically impregnate for 10 min, then mold at 3 MPa for 10 min, and finally vacuum dry at 80°C for 20 h to obtain a modified ultra-high molecular weight polyethylene fiber layer.
[0059] S3. After mixing the alicyclic epoxy resin CELLOXIDE 2021P and diallyl bisphenol A at a mass ratio of 1:5, add polyetherimide micron particles and stir at 80°C to premix evenly. Then add diphenylmethane bismaleimide micro powder and continue stirring evenly. Place the mixture on a three-roll mill for physical mixing three times. Add cresol-modified phenolic amine at a mass ratio of epoxy resin to low-temperature curing agent of 100:40 and degas under vacuum for 30 minutes to obtain the matrix resin.
[0060] S4. From the back surface to the front surface, 22 layers of modified ultra-high molecular weight polyethylene fiber, 5 layers of modified aramid fiber, and 5 layers of modified ultra-high molecular weight polyethylene fiber are sequentially laid as a transition layer, followed by 15 layers of modified aramid fiber to obtain the reinforcing fiber layer.
[0061] S5. Lay a release cloth in a vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, evacuate to 0.3MPa, inject the matrix resin of S3 into the mold through the guide pipe, so that the matrix resin uniformly wets the reinforcing fiber layer; cure at 60℃ for 3h, and cool to room temperature with the furnace to obtain the bulletproof composite material.
[0062] Comparative Example 1 (without modified aramid fiber) The difference from Example 2 is that the impact-receiving surface is composed of 14 layers of aramid fiber, and the preparation method does not include S1; otherwise, it is the same as Example 2.
[0063] Comparative Example 2 (modified aramid fiber layer without multi-walled carbon nanotubes) The difference from Example 2 is that the modified aramid fiber layer was not coated with multi-walled carbon nanotubes. The preparation method S1 is as follows: aramid fibers are treated with oxygen plasma at 150W for 5 min, then immersed in an ethanol solution of KH550 silane coupling agent with a mass concentration of 2% for 30 min, and then vacuum dried at 80°C for 1 h to obtain the modified aramid fiber layer. The rest is the same as in Example 2.
[0064] Comparative Example 3 (without modified ultra-high molecular weight polyethylene fiber) The difference from Example 2 is that the back elastic surface is composed of 20 layers of ultra-high molecular weight polyethylene fiber, and the preparation method does not include S2. All other aspects are the same as in Example 2.
[0065] Comparative Example 4 (without added toughening components) The difference from Example 2 is that the matrix resin includes bisphenol F type epoxy resin, without the addition of toughening components. The preparation method S3 is as follows: phenol-modified phenolic amine is added to the bisphenol F type epoxy resin at a mass ratio of epoxy resin to low-temperature curing agent of 100:35, and vacuum degassing is performed for 25 minutes to obtain the matrix resin. All other aspects are the same as in Example 2.
[0066] Comparative Example 5 (the toughening component only contained polyetherimide microparticles) The difference from Example 2 is that the matrix resin includes bisphenol F type epoxy resin and polyetherimide microparticles accounting for 4% of the matrix resin by mass. Preparation method S3 involves adding polyetherimide microparticles to the bisphenol F type epoxy resin, stirring and premixing evenly at 75°C, and then physically blending three times on a three-roll mill. Phenol-modified phenolic amine is added at a mass ratio of epoxy resin to low-temperature curing agent of 100:35, and the mixture is vacuum degassed for 25 minutes to obtain the matrix resin. All other aspects are the same as in Example 2.
[0067] Performance testing The following performance tests were performed on the bulletproof composite materials prepared in Examples 1-3 and Comparative Examples 1-5: Ballistic Limit Velocity (V50): Based on GJB 4300A-2012 "Test Method for Ballistic Limits of Military Ballistic Protective Materials", a 7.62mm caliber fragmentation simulated projectile (FSP, mass 1.1g, diameter 5.5mm) was used at a distance of 5m to test the V50 value of the composite material. At least 10 effective shots were fired at each sample, and the V50 value was calculated using the up-and-down method, with units of m / s.
[0068] Back convexity depth (BFS): In the V50 ballistic test, when the projectile does not penetrate the sample, the depth of the indentation (Blunt Force Trauma) in the center area of the back surface of the composite plate is measured using a high-precision laser displacement sensor. The average value of three effective impacts is taken, and the unit is mm.
[0069] Interlaminar shear strength (ILSS): Following ASTM D2344 / D2344M-2016, "Standard Test Method for Interlaminar Shear Strength of Composite Materials," the short beam shear method was used to test the interlaminar shear strength of composite materials. The specimen dimensions were 20mm × 10mm × thickness (approximately 4-6mm), with a span-to-thickness ratio of 5:1. The loading rate was 1mm / min. Five specimens were tested in each group, and the average value was taken. The unit is MPa.
[0070] Interlaminar fracture toughness (GIIc): The Type I interlaminar fracture toughness of the composite material was tested using the double cantilever beam (DCB) method, following ASTM D5528-13, "Standard Test Method for Mode I Interlaminar Crack Toughness of Non-directional Fiber Reinforced Polymer Matrix Composites". The specimen dimensions were 150 mm × 20 mm × thickness, the pre-crack length was 50 mm, and the loading rate was 2 mm / min. The GIIc value was calculated using load-displacement curves, with units of J / m. 2 .
[0071] Density: The density of the composite material was measured using the water displacement method, referring to GB / T 1463-2005, "Determination of Density of Fiber Reinforced Plastics". The unit is g / cm³. 3 The test results are shown in Table 1 and... Figure 1-2 .
[0072] Table 1 Performance test results of different bulletproof composite materials
[0073] From Table 1 and Figure 1-2 It can be seen that the V50 values of Examples 1-3 are all ≥645m / s, which are significantly higher than those of Comparative Examples 1-5. Among them, Example 2 is about 16.5% higher than Comparative Example 1 (without modified aramid) and about 19.9% higher than Comparative Example 3 (without modified ultra-high molecular weight polyethylene fiber). This indicates that the multi-scale modification of the fiber surface and the functional partitioning layered design adopted in this invention effectively improve the ballistic impact resistance of the bulletproof composite material.
[0074] The back convex depth of Examples 1-3 is ≤21.2mm, which is lower than that of Comparative Examples 1-5. After modification with nano-SiO2, fiber slippage and pull-out of the back elastic surface UHMWPE fiber are effectively suppressed, energy absorption is more complete, and back convex deformation is well controlled.
[0075] The interlaminar shear strength and interlaminar fracture toughness of Examples 1-3 are higher than those of Comparative Examples 1-5, with Example 2 achieving an ILSS of 50.2 MPa and a GIIc of 1450 J / m. 2 Compared with Comparative Example 4 (without toughening components), the toughness was improved by 34.1% and 42.2%, respectively, and compared with Comparative Example 5 (with only PEI microparticles), the toughness was improved by 17.8% and 22.9%. This indicates that the synergistic toughening system of polyetherimide microparticles and diphenylmethane bismaleimide micropowder, combined with the fiber sieve enrichment effect, significantly improves the interlayer interface toughness.
[0076] The density of the bulletproof composite materials in Examples 1-3 is all below 1.13 g / cm³. 3 It meets the requirements for lightweight protective equipment.
[0077] Therefore, the present invention adopts the above-mentioned two-phase hybrid fiber bulletproof composite material based on the optimization of the lamination sequence and its preparation method, which realizes the comprehensive improvement of the bulletproof composite material in terms of ballistic limit velocity, back convexity control, interlaminar shear strength and fracture toughness, and the process is feasible and has low density.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence, characterized in that: The bulletproof composite material is composed of a reinforcing fiber layer and a matrix resin impregnated between the layers. The reinforcing fiber layer includes a projectile-facing surface, a transition layer and a projectile-backing surface along the projectile penetration direction. The projectile-facing surface is composed of several layers of modified aramid fiber, the projectile-backing surface is composed of several layers of modified ultra-high molecular weight polyethylene fiber, and the transition layer is composed of several layers of modified aramid fiber and several layers of modified ultra-high molecular weight polyethylene fiber, which are alternately layered. The matrix resin includes epoxy resin and toughening components.
2. The two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 1, characterized in that: The modified aramid fiber layer is an aramid fiber that has been surface modified by oxygen plasma and silane coupling agent, and the surface of the modified aramid fiber layer is coated with multi-walled carbon nanotubes.
3. The two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 1, characterized in that: The modified ultra-high molecular weight polyethylene fiber layer is an ultra-high molecular weight polyethylene fiber impregnated with a nano-silica dispersion, which is an ethanol dispersion of nano-silica.
4. The two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 1, characterized in that: The toughening component accounts for 3%-5% of the mass fraction of the matrix resin. The toughening component is composed of polyetherimide micron particles and diphenylmethane bismaleimide micro powder in a mass ratio of (2-3):
1.
5. A method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence as described in any one of claims 1-4, characterized in that: Includes the following steps: S1. Aramid fibers are treated with oxygen plasma, then immersed in an ethanol solution of silane coupling agent, removed and vacuum dried to obtain a modified aramid fiber layer. Then, an ethanol dispersion of multi-walled carbon nanotubes is sprayed onto the modified aramid fiber layer and allowed to evaporate and dry naturally to obtain a modified aramid fiber layer loaded with multi-walled carbon nanotubes. S2. Place ultra-high molecular weight polyethylene fibers in a nano-silica dispersion, ultrasonically impregnate and then mold, and vacuum dry to obtain a modified ultra-high molecular weight polyethylene fiber layer. S3. After mixing the epoxy resin and allyl compound evenly, add the toughening component, mix evenly, add the low-temperature curing agent, and degas under vacuum to obtain the matrix resin. S4. A modified ultra-high molecular weight polyethylene fiber layer, a modified aramid fiber layer, and a modified ultra-high molecular weight polyethylene fiber layer are sequentially and alternately laid in a transition layer, and a modified aramid fiber layer, from the back elastic surface to the front elastic surface, to obtain a reinforcing fiber layer. S5. Lay a release cloth in the vacuum-assisted resin transfer molding mold, place the reinforcing fiber layer of S4 in the mold, arrange the guide pipe and vacuum pipeline, draw a vacuum, and inject the matrix resin of S3 into the mold through the guide pipe so that the matrix resin evenly wets the reinforcing fiber layer. Curing is carried out at a constant temperature and then cooled to room temperature in the furnace to obtain the bulletproof composite material.
6. The method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 5, characterized in that: In S1, oxygen plasma treatment is performed at 100-200W for 3-7 minutes, the mass concentration of the ethanol solution of silane coupling agent is 1%-3%, the impregnation time is 20-40 minutes, and vacuum drying is performed at 70-90℃ for 0.5-2 hours. The mass concentration of the ethanol dispersion of multi-walled carbon nanotubes was 0.8%-1.2%, and it was uniformly sprayed onto the surface of the modified aramid fiber layer using a pneumatic spray gun.
7. The method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 5, characterized in that: In S2, the mass concentration of the nano-silica dispersion is 15%-35%, the ultrasonic impregnation time is 10-15 min, the molding is performed at 1-3 MPa for 10-30 min, and the vacuum drying is performed at 70-80℃ for 20-24 h.
8. The method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 5, characterized in that: In S3, the allyl compound is diallylbisphenol A, and the mass ratio of the allyl compound to the epoxy resin is 1:(4-5). The low-temperature curing agent includes one of cashew nut shell oil modified phenolic amine, phenol modified phenolic amine, and cresol modified phenolic amine. The mass ratio of epoxy resin to low-temperature curing agent is 100:(30-40), and the vacuum degassing time is 20-30 minutes.
9. The method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 5, characterized in that: In S4, the ratio of the number of modified ultra-high molecular weight polyethylene fiber layers to the number of modified aramid fiber layers is (1-2):1, and the transition layer accounts for 20%-30% of the total number of reinforcing fiber layers.
10. The method for preparing a two-phase hybrid fiber bulletproof composite material based on optimized lamination sequence according to claim 5, characterized in that: In S5, vacuum is applied to 0.2-0.3 MPa, and the product is cured at a constant temperature of 50-60℃ for 3-4 hours.